Pengembangan Media Wayang Berbasis Kearifan Lokal untuk Meningkatkan Literasi Budaya Siswa Kelas 5 Sekolah Dasar - Setiawan, Angga (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
This research is motivated by the fact that most of the fifth grade students at SDN 1 and 2 Ngantru are not yet familiar with the cultural results of the local community, for example the Nyadran Dam Bagong culture as a traditional ceremony commemorating the history of the Menak Sopal Kingdom which once founded Trenggalek Regency, literature about culture in schools is inadequate, resulting in literacy Student culture is minimal, teachers are busy and cannot be left behind in preparing all the administration when carrying out the learning process, and the media that is often used in teaching and learning activities is only the blackboard and the methods used are only lectures, discussions and assignments. The aim of this research is to determine the effectiveness of developing wayang media based on local wisdom to increase cultural literacy in grade 5 elementary school students. The method used in this research is the R&D method with the ADDIE model. The research results obtained were through the N-Gain formula calculation score, the value of cultural literacy ability in the pretest compared with the posttest value showed that cultural literacy ability increased by 0.61. So it can be concluded that the development of wayang media based on local wisdom is effective in increasing cultural literacy in grade 5 elementary school students.